Technology and Local Language: Development of An Android-Based Sundanese-English Electronic Dictionary for The Baduy Community in Indonesia (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2024)
Although a large amount of research on Sundanese language has been conducted, little attention has been paid to technology-based Sundanese language use. Therefore, academic and practical efforts should be made to contribute to the preservation of regional language use by developing educational technology-based innovations. The purpose of this research is to develop an Android smartphone-based bilingual dictionary application to facilitate English learning and Sundanese language preservation, especially for the Baduy tribe community. This research is categorized into research and development using the Design Based Research (DBR) method. This research was conducted in four stages, namely: (1) initial analysis stage, (2) prototype design development stage, (3) trial stage, and (4) reflection stage. Research data were collected through instruments including literature studies, interviews, expert assessments, and questionnaires. Then the data was analyzed descriptively as material for developing Android dictionary prototypes to be tested and evaluated until a qualified application model was obtained. The results showed that the development of an Android smartphone-based Sundanese dictionary contributes to English learning and Sundanese language preservation. Implications and recommendations from this research and recommendations are also discussed for future research.